Drospirenone-containing oral contraceptives and venous thromboembolism: an analysis of the FAERS database - Madigan D; Shin J (Dove Medical Press, 2018)
David Madigan, Jennifer Shin Department of Statistics, Columbia University, New York, NY, USA Introduction: Substantial evidence suggests that drospirenone-containing oral contraceptives may cause a higher risk of venous thrombotic events than earlier-generation oral contraceptives. Methods: To gain insight into recent real-world implications, we conducted an analysis using the US Food and Drug Administration’s Adverse Event Reporting System. Results: Venous thrombotic events continue to be reported at a much higher rate with drospirenone-containing oral contraceptives than the general background. The disproportionality has been rising since 2010. The same behavior is not seen with levonorgestrel-containing oral contraceptives. Conclusion: Our results are consistent with decreased physician and patient awareness of risks associated with drospirenone-containing oral contraceptives. Keywords: drug safety, Yaz, venous thrombotic events, FDA adverse event reporting system, disproportionality